Is beef quality affected by the inclusion of distiller grains in cattle diets? - Merayo, Manuela (2022)
This study aimed to analyze the effect of including increasing levels of distiller grains (DG) in beef cattle feeding diets on meat quality from an integral approach. To this end, we analyzed the meat from 36 yearling steers fed with four dietary treatments: 0DG (control corn-based diet), 15DG, 30DG, and 45DG (containing 15%, 30%, or 45% of DG on DM basis). Crude protein, ash, and fat contents of diets increased with DG level. The fatty acid profile of DG diets was reflected in the fatty acid profile of plasma samples. Feeding diets with DG had no effect on the biochemical parameters analyzed in plasma. In addition, it did not influence the water holding capacity, the muscle or fat color at 72 h post mortem or at retail display, or the contents of SFAs, MUFAs, and PUFAs in beef. The DG diets led to lower values of cooking loss. Meat from 15DG and 30DG showed greater percentage of troponin C and fragments of 30 to 27 kDa than meat from 45DG. Also, meat from 30DG showed the lowest values of Warner-Bratzler shear force. Hence, including up to 30% corn DG in beef cattle feeding diets had positive effects on meat quality. // Resumen: Este estudio tuvo como objetivo analizar el efecto de incluir niveles crecientes de granos de destilería (DG) en dietas de alimentación de bovinos de carne sobre la calidad de la carne desde un enfoque integral. A esto Para finalizar, analizamos la carne de 36 novillos alimentados con cuatro tratamientos dietéticos: 0DG (dieta de control a base de maíz), 15DG, 30DG y 45DG (que contienen 15%, 30% o 45% de la DG sobre la base de DM). Los contenidos de proteína bruta, cenizas y grasa de las dietas aumentaron con nivel de GD. El perfil de ácidos grasos de las dietas DG se reflejó en el perfil de ácidos grasos de muestras de plasma La alimentación de dietas con DG no tuvo efecto sobre los parámetros bioquímicos analizada en plasma. Además, no influyó en la capacidad de retención de agua, la el color del músculo o la grasa a las 72 h post mortem o en la exhibición al por menor, o el contenido de los SFA, MUFA y PUFA en la carne de res. Las dietas DG condujeron a valores más bajos de pérdida por cocción. Carne de 15DG y 30DG mostró mayor porcentaje de troponina C y fragmentos de 30 a 27 kDa que la carne de 45DG. Además, la carne de 30DG mostró la menor valores de la fuerza cortante de Warner-Bratzler. Por lo tanto, incluir hasta un 30 % de GD de maíz en la carne de res Las dietas de alimentación del ganado tuvieron efectos positivos en la calidad de la carne.